If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
3*x+x/30-(12/6) = x/5-1 // - x/5-1
3*x+x/30-(x/5)-(12/6)+1 = 0
3*x+x/30-(x/5)-2+1 = 0
17/6*x-1 = 0 // + 1
17/6*x = 1 // : 17/6
x = 1/17/6
x = 6/17
x = 6/17
| 12x+18=2(6x+3) | | 9x=8(3x+5) | | 5/7(x+1)=1/21(x+6) | | -4=(-4m+9+m)3-13 | | 4x+9=47/5+3x | | 14x^3+(3x+8x^3)= | | 9x^2+270=0 | | 94-5x=13x+16 | | 16x-(3x-7)=12 | | -5/6x+1=5/18 | | 3y+12=3(4+y) | | -(-5+5p)+6p=-8 | | 8=15-c/3 | | y=7-(1) | | y=7-(0) | | 3p-1=5(9-1) | | 21-7b=-4+5(8b+5) | | y=7-(-1) | | 4(3x-6)=24 | | 6-10x=56-24x | | .5(12x-4)+6=14-10x | | y=-3(3) | | 2(6x-6)=72 | | 14x-(9x-3)=30 | | 1/2*9/2 | | 2ab+4a= | | 7(8+4x)=364 | | 4u=70-3u | | -8(3+r)=-29-7r | | -2(d+5)=-6 | | 82-5x=2x+15 | | 5x+16/9=x/3 |